EFFECT OF GnRH DURING VARIOUS STAGES OF ESTRUS CYCLE ON FERTILITY AND PLASMA PROGESTERONE IN BUFFALOES - MANDAL, D D; SRIVASTAVA, S K; KUMAR, P (The Indian Journal of Animal Reproduction, 2023)
This study was aimed to see the effect of GnRH administration on progesterone profile and conception in buffaloes. Forty parous buffaloes were divided into five groups each of eight animals. Animals in group I, II and Ill were administered GnRH (2.5 ml. Receptal) on day-0, day-5 and day-12 of estrus cycle, respectively, whereas group IV animals received same dose of GnRH on all three days, ie day-0, 5 and 12 of cycle. Group V received normal saline on the same days as above and served as control. Progesterone concentration was significantly higher (P<0.05) in group I on days 12, 13 and 21 , whereas in group 11, Ill and IV from day 6 to 21 compared to control. Although P4 was higher in all the four treatment groups than control, but it was significantly higher (P<0.05) among the animals of group 111 and IV compared to group I and 11 also on day 21. Similarly conception rate was also higher in the animals of all the treatment groups but significantly higher (P<0.05) in group Ill and IV than group I, II and control. Service per conception was also significantly lower (P< 0.05) in group Ill and IV than control group. lnspite of three times GnRH administration in group IV animals, conception rate was similar to group Ill animals. Thus the study reveals that single GnRH administration at day 12 might be sufficient for improvement of conception in buffaloes.